Behaviour of endangered European eels in proximity to a dam during downstream migration: Novel insights using high accuracy 3D acoustic telemetry. Issue 2 (29th October 2019) - Trancart, Thomas; Carpentier, Alexandre; Acou, Anthony; Danet, Valentin; Elliott, Sophie; Feunteun, Éric
Abstract: River infrastructures such as weirs, hydropower stations or water reservoirs represent obstructions to migration for diadromous fish. Knowledge of accurate behaviour of fish in front of such structures is required to protect migrants from hazardous areas, guide them towards safe passage or adapt structure to improve the escapement. We developed and made available a method to process acoustic telemetry data based on Time Difference Of Arrival analysis to accurately locate tagged fish. Improved accuracy allows the detection of escape routes and description of dam‐crossing tactics. Sixteen tagged eels were tracked with high accuracy (1–2 m) and ~1 location min −1 frequency during their exploration period on reaching the dam. Two migration routes (spillways and bottom compensation flow pipe) were used by 77% and 23% of eels respectively. Spillways were the preferred route, but a median of 16 days were required to pass the dam versus 1.1 days via the compensation pipe. A minimal water crest of 40 cm was required for passage via spillways. Eels passing through the compensation pipe were exclusively nocturnal and mainly explored the bottom of the dam. Eels passing through spillways explored the whole dam area by night and day, and were not attracted to the compensation pipe entrance. With global warming, more frequent drought periods are expected, potentially leading to decreased opportunities for eels to migrate across safer dams by spillways. To conserve this endangered species, dam management strategies that account for expected hydrologic conditions and distinct exploration behaviours are needed.